Populärkulturella ikoner: En introduktion - Klinkmann, Sven-Erik (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2009)
In this special issue questions of how to interpret popular-cultural icons are addressed by several researchers. These kinds of icons are understood as highly enigmatic, representing a middle ground between mimesis and fantasy making theory and research about them especially tricky. Icons are played out in a space involving changing media technology, visibility, storytelling and reception (by fans and others). Several popular musical icons — Frank Sinatra, Dolly Parton, Beatles, Morrissey, Pete Doherty, Genesis and Spice Girls — are discussed, using a variety of theories and methods in order to bring more light on this complex phenomenon.